TFG-Net:Tropical Cyclone Intensity Estimation from a Fine-grained perspective with the Graph convolution neural network. (February 2023) - Xu, Guangning; Li, Yan; Ma, Chi; Li, Xutao; Ye, Yunming; Lin, Qingquan; Huang, Zhichao; Chen, Shidong
Abstract: Tropical Cyclone Intensity Estimation (TIE) is a fundamental study subject for tropical cyclone development, flood or landslide avoidance, etc. Despite considerable efforts, two main challenges remain unresolved in this critical endeavor. The first challenge is that the TIE task is frequently conducted as a coarse-grained recognition problem rather than a fine-grained one. The second challenge is that the prediction fails to consider general wind speed information. To conquer these two challenges, we offer a novel model, namely Tropical cyclone intensity estimation from a Fine-grained perspective with the Graph convolution neural Network (TFG-Net). It is composed of three key components, viz., the Backbone, the Fine-grained Tropical cyclone Features Extractor (FTFE), and the Wind Scale Transition Rule Generator (WTRG), which aim at extracting general spatial features, subtle spatial features, and general wind speed information, respectively. To validate the proposed method, extensive experiments on a well-known real-world tropical dataset named GridSat were carried out. Following the standard benchmark task setting that the model estimates the wind speed from a given satellite image, the proposed TFG-Net reaches 11.12 knots in the RMSE metric, which outperforms 33.33%, 2.54% to the traditional method and the state-of-the-art deep learning method, respectively. The code is available on GitHub: https://github.com/xuguangning1218/TI_Estimation and its reproductive result is available on Code Ocean: https://doi.org/10.24433/CO.6606867.v1 . Highlights: We first proposed to conduct cyclone intensity estimated in fine-grained perspective. We propose to divide predictive wind speed into general part and particular part. Extensive experiments and analysis are conducted on the real-world dataset.